SET PHRASES WITH THE LEXEME ‟THURSDAY”. CONSIDERATIONS REGARDING THE LINGUISTIC AND CULTURAL IMAGE OF THE DAYS OF THE WEEK IN THE POLISH AND ROMANIAN FOLK CALENDAR - PORAWSKA, Joanna (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Set Phrases with the Lexeme ”Thursday”. Considerations Regarding the Linguistic and Cultural Image of the Days of the Week in the Polish and Romanian Folk Calendar. Ever since the 1970s and 1980s, the relationship between language and culture has been a topic of broad interest for linguists, which undoubtedly contributed to bringing linguistics closer to humanities. The prefix ethno- contained in the term ethnolinguistics used over the course of this article should be interpreted as an abbreviation for ethnology, a term synonymous with the American anthropology. Describing so-called language stereotypes is one of the main topics of interests for what we generally call “Polish cognitivism”, conducted for years by Polish linguists. The term stereotype itself is used in its original Lippmann's meaning as a schematic and one-sided “picture or image in a person’s mind” of a phenomenon, human being, or thing and at the same time an opinion assimilated from the environment even before discovering the object itself. In Polish language and culture, days of the week were not personified. Therefore, to a philologist-linguist who is comparing the two languages, the data derived from folklore will be a “weaker” starting point than “hard” linguistic confirmations (fixed structures). My goal is to offer a Polish and Romanian comparative analysis which is supported by ethnological or historical data. Frazeologisme conținând lexemul „joi”. Consideraţii privind imaginea cultural-lingvistică a zilelor săptămânii în calendarul popular polonez şi în cel românesc. Începând cu anii 1970-1980, relația dintre limbă și cultură a reprezentat o temă de larg interes pentru lingviști. Prefixoidul ethno-, conținut în termenul etnolingvistică, așa cum este utilizat în acest articol, ar trebui interpretat ca o abreviere de la etnologie, un termen sinonim celui de antropologie în cultura americană. Descrierea așa-numitelor stereotipuri lingvistice reprezintă una dintre temele predilecte ale curentului cunoscut sub numele de cognititivism polonez. Termenul stereotip este utilizat în sensul său original, ceea ce Lippmann numește „o imagine schematică, unilaterală în mintea cuiva” asupra unui fenomen, ființe sau lucru și, de asemenea, o opinie asimilată din mediul în care ne aflăm, chiar înainte de a descoperi obiectul în sine. În limba și cultura poloneză, zilele săptămânii nu sunt personificate. Prin urmare, pentru un filolog care compară cele două limbi, datele culese din folclor reprezintă un punct de plecare „mai slab” decât dovezile lingvistice „tari”, sub forma structurilor fixe. Obiectivul nostru aici este să oferim o analiză comparativă între română și polonă, sprijinită de date etnologice și istorice. Cuvinte-cheie: etnolingvistică, cercetări comparate polono-române, calendar popular, ziua de joi Article history: Received 28 December 2022; Revised 24 February 2023; Accepted 28 February 2023; Available online 27 March 2023; Available print 31 March 2023.